Integrasi Karakter Moral dan Karakter Kinerja dalam Pembelajaran di Madrasah Aliyah Negeri Gorontalo - Athiyah, Cut N. Ummu; Umar, Roslan (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2023)
This research aims to identify and examine the integration of moral and performance characters within the MAN Insan Cendikia Gorontalo (ICG) learning process. It focuses on intracurricular, co-curricular, extracurricular, and hidden curriculum methodologies. Data was collected through observations, interviews, and documentation studies using a descriptive-analytical approach. It was complemented by referencing secondary resources like articles and expert publications. The findings indicate that MAN ICG adopted the